Interprofessional Learning: Medical and Nursing Students Experience of Participating in Breast Cancer Awareness Workshop - Rajani Ranganath; Miriam Simon; John Muthusami (Mashhad University of Medical Sciences, 2023)
Background: The purpose of the study was to analyse interprofessional learning experience and the overall experience of the breast cancer awareness workshop among undergraduate medical and nursing students.   Method: This was a cross-sectional study using mixed method design. The study was carried out for medical students of College of Medicine and Health Sciences, National University of Science and Technology, Oman and nursing students of Sohar Nursing Institute and the North Batinah Nursing Institute in November 2019. A total of 170 students attended the breast cancer awareness workshop. Out of which 105 (55 -medical and 50 - nursing) students filled the post workshop survey questionnaire. Thematic content analysis was done for open ended questions and quantitative type questions were analysed using SPSS software version 22. Results: The feedback survey looked on four domains of learning experience 1) Interprofessional experience: students of nursing (54.8%) preferred to have frequent inter-professional training sessions when compared to medical students (6.2%) (P-value<0.001). 2) Teaching-learning strategies used: Hand-on activities (Breast self-examination activity on breast model method) was more preferred method when compared to others. 3) Personal: Students expressed to have improved knowledge on breast cancer and breast self-examination. 4) Overall experience: 96.1 % students agreed that the workshop was organized well and 98% felt the information was presented clearly.       Conclusion: Interprofessional education is essential for collaborative practice in future which is important for quality of care and patient safety. Breast cancer and breast self-examination awareness programs can be a convenient way of initiating interprofessional education among health care students.